Analisis Pengaruh Indeks Harga Konsumen Terhadap Inflasi: Studi Kasus Pada Inflasi Kota Palangka Raya dan Kab. Sampit di Kalimantan Tengah - Vivy Kristinae (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2018)
Palangka Raya and Sampit is a city in Central Kalimantan. These two cities have experienced inflation several times. And the purpose of this study is to find out whether the CPI (Consumer Price Index) of cities in Palangka Raya and Sampit has an influence on rising inflation. Is study used a quantitative approach to data processing and multiple linear regression for its analysis. The research method used is by analytical descriptive method that is technique trying to collect data in accordance with the actual situation, present and analyze so as to provide a fairly clear comparison of the object under study which than cab be drawn a conclusion. And the result of this study is that inflation is significantly affected by CPI from the city of Palangka Raya and Sampit.